2016
DOI: 10.4103/0972-9941.170018
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised controlled trial comparing chronic groin pain and quality of life in lightweight versus heavyweight polypropylene mesh in laparoscopic inguinal hernia repair

Abstract: BACKGROUND:The aim of our study was to compare chronic groin pain and quality of life (QOL) after laparoscopic lightweight (LW) and heavyweight (HW) mesh repair for groin hernia.MATERIALS AND METHODS:One hundred and forty adult patients with uncomplicated inguinal hernia were randomised into HW mesh group or LW mesh group. Return to activity, chronic groin pain and recurrence rates were assessed. Short form-36 v2 health survey was used for QOL analysis.RESULTS:One hundred and thirty-one completed follow-up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31] Agarwal et al in 2009, Prakash et al in 2016, and Kalra et al in 2017 presented the mean score on the Visual Analogue Scale (VAS) AE the standard deviation (SD); however, they did respond to the request for the additional data required for meta-analysis. [32][33][34] Eight 16)…”
Section: Chronic Pain-any Pain and Severe Painmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30][31] Agarwal et al in 2009, Prakash et al in 2016, and Kalra et al in 2017 presented the mean score on the Visual Analogue Scale (VAS) AE the standard deviation (SD); however, they did respond to the request for the additional data required for meta-analysis. [32][33][34] Eight 16)…”
Section: Chronic Pain-any Pain and Severe Painmentioning
confidence: 99%
“…Ultrapro (28) and TiMesh (35) Vypro II (30) and TiMesh (35) Prolene soft (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Ultrapro ( 28) Ultrapro ( 28) Ultrapro ( 28 of these 11 studies reported severe pain results, albeit with varying definitions (Table 1A). 18,24,[26][27][28][29][32][33][34] The risk of any pain showed no significant difference when using a LWM (123/1362 patients) compared with a HWM (127/1277 patients) (RR 0.79, 95% CI: 0.52-1.20) (Fig. 2).…”
Section: Chronic Pain-any Pain and Severe Painmentioning
confidence: 99%
“…The pore size was reported in 13 studies (9-11, 14, 18, 20, 22, 23, 28, 50-53) (Figure 2B). Two studies described that the lightweight mesh had large pore size without specifying the size in mm (10,22), while the remaining ten studies either reported the pore diameter in mm or in µm, which was converted to mm (one study informed the size by email ( 23)) (9,11,14,18,20,23,(50)(51)(52)(53). Two studies had unspecified pore sizes (9,53) and two studies used a range (14,28).…”
Section: Lightweight Meshmentioning
confidence: 99%
“…Two studies described that the lightweight mesh had large pore size without specifying the size in mm (10,22), while the remaining ten studies either reported the pore diameter in mm or in µm, which was converted to mm (one study informed the size by email ( 23)) (9,11,14,18,20,23,(50)(51)(52)(53). Two studies had unspecified pore sizes (9,53) and two studies used a range (14,28). Nevertheless, the median of all lightweight meshes was 1.6 mm with an IQR of 1.0-2.3 mm and a range of 1.0-4.0 mm.…”
Section: Lightweight Meshmentioning
confidence: 99%
See 1 more Smart Citation